DUAL STAINING CYTOLOGY WITH P16/KI67 FOR CERVICAL CANCER SCREENING - Milkovski, Daniel; Stojovski, Marjan; Jovanovska, Viktorija; Kijajova, Ivana; Gjirevski, Vlatko; Mirakovska, Maja Koteva; Joksimovic, Marija (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Currently, cytology, HPV testing, and combined cytology with HPV testing are the methods used for cervical cancer screening in patients. The p16/Ki67 dual staining is a biomarker with high sensitivity and specificity for CIN2+ lesions. The introduction of such a biomarker for triage and identification of high-grade cervical lesions in patients, based on preliminary results from cytology and HPV screening, is necessary to prevent an excessive number of referrals for colposcopy and biopsy. The study was designed as a cross-sectional cohort study conducted at the University Clinic of Gynaecology and Obstetrics, Skopje, over a two-year period, involving a group of 81 patients aged 21 to 65 years. All patients underwent HPV DNA testing with typing, cytological testing (LB), and p16/Ki67 dual staining. The correlation of p16/Ki67 immunocytochemical status in patients with cytological verified squamous intraepithelial lesions and the presence of high-risk HPV was analysed. The analyses revealed a significant association between high-grade cervical lesions and p16/Ki67 staining status. A positive result from p16/Ki67 dual staining was significantly associated with an HSIL finding on the Pap test (p=0.01). HSIL cytological findings were significantly more common in patients with positive immunocytochemistry (36.36% vs 5.71%). Patients positive for p16/Ki67 dual staining had more frequent positive HPV typing compared to patients with negative p16/Ki67 staining. Keywords: p16/Ki67, immunocytochemistry, cervical cancer screening, HPV